PENGARUH PROFITABILITAS, KEPEMILIKAN KELUARGA, CORPORATE GOVERNANCE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK DI INDONESIA (Studi Empiris Pada Perusahaan food and beverage yang terdaftar di Bursa Efek Indonesia periode 2015-2018) - Lutvia Yanda Ayunanta; M. Cholid Mawardi; Anik Malikah (Universitas Islam Malang, 2020)
The purpose of this study was to determine the effect of profitability, family ownership, corporate governance, and institutional ownership on tax avoidance. The population of this study is the food and beverage companies listed on the Indonesia Stock Exchange in 2015-2018, the number of samples obtained by purposive sampling technique is 11 companies. The type of data used is secondary data by using the method of data collection. The method of analysis in this research is multiple regression analysis. The results of this study indicate that profitability has a significant effect on tax avoidance. Family ownership has a significant effect on tax avoidance. Independent commissioners have a significant effect on tax avoidance. The audit committee has a significant effect on tax avoidance. Institutional ownership has a significant effect on tax avoidance.Keywords : profitability, Family Ownership, Corporate Governance, Institutional Ownership.